Participatory Budgeting in Indonesia: from the Policy Innovation to the Democracy Innovation - Mochamad Arif Affandi; Kacung Marijan; Dwi Windyastuti (The Journal of Society and Media, 2022)
Community participation in the government budgeting process provides opportunities for wider and deeper public participation. This paper uses a systematic literature review method with a meta-synthetic approach that aims to examine the practice of participatory budgeting (PB) in Indonesia by comparing PB programs in the early reform era with PB programs in the reform era. The results show that the PB model in the early era of World Bank-sponsored reforms such as the Musrenbang (PNPM and KDP) is a technocratic administrative policy innovation because it has standard rules, innovation comes from the government and the community becomes the object of government policy. In addition, this study also finds that Prodamas indirectly strengthens Musrenbang because of its participation at the RT level. People at the lowest level are encouraged to participate more. Therefore, the researcher hopes that Regional Regulations have greater power.